Lead acetate deteriorates the improvement effect of L-arginine and tetrahydrobiopterin on endothelin-1 receptors activity in rat aorta (Baghdad Science Journal, 2023)
Endothelin-1 (ET-1) is a potent vasoconstrictor hormone that has been identified as an important factor responsible for the development of cardiovascular dysfunctions. ET-1 exerts its vasoconstrictor activity through two pharmacologically distinct receptors, ETA and ETB that are found in vascular smooth muscle cells (VSMCs) and the vasodilator activity through an ETB receptor located on endothelial cells. This study aimed to show the impact of 1µM L-arginine (LA), 100µM tetrahydrobiopterin (BH4), and their combined effect on ET-1 activity in both lead-treated and lead-untreated rat aortic rings. This means, investigating how endothelial dysfunction reverses the role of nitric oxide precursor and cofactor. In this study, Rat aortic rings have been pre-incubated with BH4, LA and their combination. Subsequently, the aortic rings were preincubated with 200µM N-Nitro-L-arginine methyl ester (L-NAME) and 0.5µM BQ-123. Then, the vascular response to cumulative doses of rat ET-1 was analyzed in each of the above-mentioned groups (LA, BH4, LA & BH4, L-NAME, BQ-123), in the presence and absence of lead acetate 1µM Pb (C2H3O2)2. ET-1 efficacy and potency were significantly decreased in the presence of LA, BH4, and LA and BH4 combination in the untreated group, while it significantly increased in the presence of lead. In the second trial of experiments ET-1 efficacy markedly decreased in BQ-123- incubated cells in both lead-treated and untreated aortic rings. In the presence of lead, the efficacy of ET-1 was raised with the use of L-NAME. In conclusion, LA and BH4 can be considered pharmacological agents to alter the potency of ET-1-induced vasoconstriction and concomitantly lower blood pressure.